Toward global and national toxicity footprints - Leclerc, Alexandra; Berthet, Etienne; Stadler, Konstantin; Wood, Richard; Laurent, Alexis (Journal of industrial ecology, 2023)
Estimating comprehensive toxicity footprints, encompassing potential impacts of toxic releases from consumption on human health and ecosystems, remains challenging due to the absence of complete emission inventories and disaggregation in global economic sectors. This study proposes an integrative approach to evaluate the global toxicity footprint by combining multiple databases, inventorying methods gap‐filling/extrapolation techniques, and environmentally extended multi‐region input–output models. We incorporated industrial, residential, and agricultural emissions of 693 chemicals into air, water, and soil, assessing the toxicity footprints of 49 countries and regions and revealing the displacement of toxic impacts across regions and nations. Our results emphasize the significant sensitivity of emission inventories and toxicity footprints to the choice of extrapolation procedures in regionalized chemical inventory development. Despite considerable progress in consolidating emission data, major gaps persist in publicly available datasets, impeding accurate extrapolation of global pollutant releases and comprehensive analysis of toxicity footprints. Primary data require refinement, harmonization, and expansion to enhance toxicity footprints' accuracy, particularly concerning pesticide emissions and national Pollutant Release and Transfer Registers initiatives. This study offers crucial insights for national and regional policymakers, facilitating the creation of targeted regulations and incentives to mitigate toxic substances' environmental impact. Future research should prioritize developing input–output table projections, deriving forward‐looking time series of national emission inventories, and establishing absolute thresholds for toxic impacts within the framework of environmentally sustainable societies.